Preparation, characterization and heat transfer analysis of nanofluids used for engine cooling. (September 2019) - Kumar, Aditya; Subudhi, Sudhakar
Highlights: Preparation and characterization of nanofluids for engine coolant have been discussed. Effects of properties like thermal conductivity and viscosity are studied. Review of heat transfer analysis using Nusselt number is deliberated. Challenges & future of nanofluids as coolant are emphasized. Abstract: The car radiators or any vehicle engine thermal management system is evolving since its beginning, to achieve a sustainable, energy efficient stage. In this peculiar journey, the nanofluids playing a vital role of coolants to enhance the exchange rate of heat transfer to make the radiator cooling system effective. The current article is summarized and talk over radiator cooling of engine in vehicles using nanofluids. The nanoparticles present in the nanofluids have higher thermal properties which contributes to higher heat transport. The article opens with the introduction of the nanofluids, coolants and a summarized evolving history of a car radiator. The next sections include the overview of synthesis and characterization of nanofluids based on engine coolant followed by the heat transfer analysis. Effects on the thermophysical property (Thermal conductivity and Viscosity) of fundamental parameters which can be avoidable while selecting parameters are discreetly discussed. The fundamental of convective heat transfer and the mechanism behind the change in convective heat transfer is discussed with non-dimensional numbers. A number of suggestion and guidelines are reported for the better performance and results with nanofluids. The article provides an essential assessment of the nanofluids in the radiator cooling and the paper also provide a detail guideline for the development of amicable future of nanofluids in the heat transfer application.